1996
DOI: 10.1111/j.1600-0447.1996.tb09881.x
|View full text |Cite
|
Sign up to set email alerts
|

A double‐blind randomized placebo‐controlled study of the efficacy and safety of pirlindole, a reversible monoamine oxidase A inhibitor, in the treatment of depression

Abstract: The efficacy and safety of pirlindole (300 mg/day), a new reversible inhibitor of monoamine oxidase A, have been evaluated in a multicentre placebo-controlled double-blind randomized trial in 103 in-patients suffering from unipolar major depression (DSM-III-R 296.2, 296.3) over a 42-day period after a run-in placebo period of 6 days. Pirlindole produced a significantly greater decrease than placebo in the Hamilton depression score (from day 28), the Hamilton anxiety score (from day 28) and the Montgomery-Asber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 13 publications
1
2
0
2
Order By: Relevance
“…However, the frequency of dry mouth and tachycardia was significantly greater in the moclobemide group (19% and 15%, respectively) compared to the pirlindole group (6% and 4%, respectively). These results confirm the findings of the most recent study conducted with pirlindole vs. placebo, in which the frequency of dry mouth and tachycardia associated with pirlindole treatment was 2% and 0%, respectively (20). They also confirm the findings of the majority of studies conducted with moclobemide, in which the frequency of tachycardia ranges from 5 % (28) to 11% (29), and the frequency of dry mouth ranges from 17% (30) to 33% (29).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, the frequency of dry mouth and tachycardia was significantly greater in the moclobemide group (19% and 15%, respectively) compared to the pirlindole group (6% and 4%, respectively). These results confirm the findings of the most recent study conducted with pirlindole vs. placebo, in which the frequency of dry mouth and tachycardia associated with pirlindole treatment was 2% and 0%, respectively (20). They also confirm the findings of the majority of studies conducted with moclobemide, in which the frequency of tachycardia ranges from 5 % (28) to 11% (29), and the frequency of dry mouth ranges from 17% (30) to 33% (29).…”
Section: Discussionsupporting
confidence: 89%
“…Pirlindole is a tetracyclic compound that has been characterized as a potential antidepressant drug in preclinical studies (16)(17)(18), and in which interest has been shown due to its marked selectivity as a RIMA (19). In clinical trials, the efficacy and safety of pirlindole have been demonstrated compared to placebo (20) and to reference standard drugs such as maprotiline (21), imipramine (22, 23), amitriptyline (23)(24)(25), desipramine (26) and mianserin (27).…”
Section: Introductionmentioning
confidence: 99%
“…Безопасность и эффективность антидепрессивной те-рапии пирлиндолом неоднократно подтверждалась в различных зарубежных и отечественных исследованиях, в том числе, и среди пациентом с кардиальной пато-логией [6,9]. Однако попытка терапии депрессий лег-кой и умеренной степеней тяжести у пациентов с сер-дечно-сосудистыми заболеваниями антидепрессан-том пирлиндол как вмешательства, направленного на повышение приверженности этих пациентов к лечению препаратами кардиологического профиля ранее не производилась, в связи с чем опыта применения с этой целью антидепрессантов вообще, и пирлиндола в частности, нет.…”
Section: Discussionunclassified
“…Однако попытка терапии депрессий лег-кой и умеренной степеней тяжести у пациентов с сер-дечно-сосудистыми заболеваниями антидепрессан-том пирлиндол как вмешательства, направленного на повышение приверженности этих пациентов к лечению препаратами кардиологического профиля ранее не производилась, в связи с чем опыта применения с этой целью антидепрессантов вообще, и пирлиндола в частности, нет. Считается, что для эффективной анти-депрессивной терапии требуется лечение в течение 4-6 мес (минимум) [5,6,9]. В нашем исследовании в тече-ние 1 мес антидепрессивную терапию продолжили 24 (75%) пациента, в течение 2 мес -2 (6%).…”
Section: Discussionunclassified
“…Pirlindole (PIR, pirazidole; 1,10‐trimethylene‐8‐methyl‐1,2,3,4‐tetrahydropyrazino [1,2,‐a] indole hydrochloride) is a tetracyclic compound that has been characterized as a potential antidepressant drug (de wilde et al ., 1996; Bruhwyler et al ., 1997; Tanghe et al ., 1997). The main mechanism of action of PIR consists of a selective and reversible inhibition of the MAO type A (MAO‐A) (Medvedev et al ., 1992; 1996; Bruhwyler et al ., 1997).…”
Section: Introductionmentioning
confidence: 99%